Influence of incremental pre-strain on corrosion behavior of Al-Zn-Mg powder metallurgy alloy during hot forging. (July 2023) - Krishna, Katika Hari; Davidson, M J; Rajmohan, K S; Bharat, Nikhil
The interaction of pre-strain and corrosive medium can either accelerate or decelerate material failure. In the present study, the electrochemical activity of forged preforms is assessed by the open circuit potential (OCP), potentiodynamic polarization, and electrochemical impedance spectroscopy (EIS). A powder metallurgy route was used to fabricate Al-5.6Zn-2Mg alloy with 0.8 relative density. The fabricated alloy was subjected to hot axial forging at various temperatures such as 300°C, 400°C, and 500°C under a 0.005/s strain rate. The microstructure and corrosion morphologies of sintered and forged preforms under various deformation levels and temperatures were investigated using scanning electron microscopy (SEM). After the deformation process, flow behavior, densification behavior, and electrochemical behavior are studied. Deformation behavior (true strain was linked to the local mechanical properties (hardness) and electrochemical properties (pitting potential (Epit )). The potentiodynamic polarization results showed that as the degree of deformation increased, there was a decrease in the corrosion current density and an increase in the pitting potential. Al-5.6Zn-2Mg corrosion resistance significantly improved with a degree of deformation and temperature. A mathematical model relating corrosion rate and true strain for various deformation temperatures is developed to estimate the corrosion rate for any true strain. Pitting corrosion was observed in deformed preforms as a corrosion mechanism. Because of the increased deformation degree and temperature, the corrosion morphologies showed the closing of pores.